Effectiveness Of The Community Radio Station Management In Nontaburi Province. - Ngamsangha, Taweesak (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The objectives of the study were threefold : 1) to investigate the administrative practices impinging upon the effectiveness of the community radio stations in Nontaburi Province ; 2) to ascertain the factors conducive to the administrative effectiveness ; and 3) to recommend for the improvement of the factors influencing the administrative effectiveness of the above community radio stations. The study was qualitative in nature. The needed data were mainly collected from in-depth interviews with key informants comprised of the following persons : directors of the radio stations, technical staff members, and radio programmers, radio station operators of the community radio stations in Nontaburi Province; and the community radio listeners. Finally, the collected data were qualitatively analyzed in the following manner : categorizing , systematizing, interrelating, synthesizing , storytelling, and summarizing. And it was found from the study that : . 1. With regard to the effectiveness of the administrative practices of the community radio stations, it could be generally said that every community radio station in Nontaburi Province was required to operate and manage by the administrative committee; the committee members were representatives of the community members or stakeholders. The policy of the community radio stations was clearly defined in writing. The policy implementation was participatory in nature and accompanied by financial and technical support. Above all, administrative practices were carried out according to the conditions stipulated by law. In this regard, the training of personnel and those concerned to keep them well informed about the rules and regulations as well as the operation of the community radio stations was of vital importance. 2. With respect to factors influencing the effectiveness of the community radio station administration, by and large, the adoption of Western culture led to the change in attitudes and values of Thai people to a great extent. The advances in mass communication have great impact on the economy in the sense that radio waves and the like have created the economic values of themselves , as well as the economic values of goods and services. Moreover, radio waves have played a dominant role in keeping law and order or security of the country . It is so simply because community radio stations are required by law to use radio waves for the national security as well. 3. Based on the research findings, the researcher has made the following recommendations: The community radio stations in Nontaburi Province should operate the stations in line with the laws pertaining to the operation of community radio stations as well as with the code of conducts. In addition , the community radio stations must deal fairly with the complaints made by the community radio listeners ; the radio stations must settle disputes among community radio operators with justice and fairness; the stations should make all possible efforts to enhance the capabilities of all community radio stations in Nontaburi Province ; the radio stations operators should be well informed about the best practices of the community radio stations ; the stations are obligated to encourage the local people to get involved in the operation in the ways that are deemed desirable and are accordance with the morality and ethics of Thai people. Finally, the stations should make attempts to encourage all the stations and the people in the localities to monitor with each other so as to enable the community radio stations to administer their stations in such a way that they bring about desirable and sustainable public interest in the years to come. Article history : Accepted 24 February 2017 SIMILARITY INDEX = 0.00